2020
DOI: 10.21037/qims.2020.02.17
|View full text |Cite
|
Sign up to set email alerts
|

The optimal monoenergetic spectral image level of coronary computed tomography (CT) angiography on a dual-layer spectral detector CT with half-dose contrast media

Abstract: Background: To investigate the optimal monoenergetic level of spectral reconstructions in coronary computed tomography angiography (coronary CTA) on a dual-layer spectral detector computed tomography (SDCT) with half-dose contrast media.Methods: Two hundred patients with suspected coronary artery disease (CAD) were enrolled in this prospective coronary CTA study and randomly divided into a routine-dose contrast media group and a half-dose contrast media group (each n=100). Coronary CTA was performed using SDCT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 47 publications
1
22
1
1
Order By: Relevance
“…This study also revealed a negative correlation between HDL and CAD incidence, which was consistent with several epidemiological studies (14)(15)(16). Theoretically, HDL's main physiological function is to reverse cholesterol transport by transporting cholesterol from peripheral tissues to the liver, from which point the cholesterol will be broken down and excreted as bile (16)(17)(18). This metabolic process is the basis for the prevention effect of HDL in CAD, and this theory can be used to explain the conclusions of this study.…”
Section: Discussionsupporting
confidence: 88%
“…This study also revealed a negative correlation between HDL and CAD incidence, which was consistent with several epidemiological studies (14)(15)(16). Theoretically, HDL's main physiological function is to reverse cholesterol transport by transporting cholesterol from peripheral tissues to the liver, from which point the cholesterol will be broken down and excreted as bile (16)(17)(18). This metabolic process is the basis for the prevention effect of HDL in CAD, and this theory can be used to explain the conclusions of this study.…”
Section: Discussionsupporting
confidence: 88%
“…Furthermore, SDCT is a novel spectral CT technology which can provide polychromatic images and a variety of spectral reconstructions from the same examination using standard CT protocols, allowing for retrospective spectral imaging analysis (27). SDCT can also be used to obtain VMI at low energy levels with low levels of noise and a high contrast-to-noise ratio (CNR), because the dual-layer detector can facilitate the exploitation of anti-correlated noise suppression due to perfectly matched raw-data and effectively suppresses image noise (26,28). Therefore, low-energy VMI, such as 40 keV, based on SDCT could be well used in clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…Previous research has attempted to assess the accuracy and precision of vessel lumen area measurements with conventional CT [11], but no data exist regarding dual-energy/spectral image reconstructions. Some studies recommend various low-or mid-energy VMI for CCTA [12][13][14], but to our knowledge, segmentation reliability for vessel lumen area quantification has not been evaluated yet. VMI have different contrast and noise characteristics than conventional CT images; since spatial resolution strongly depends on contrast and noise [15,16], increased image noise may be a concern for vessel lumen quantification tasks.…”
Section: Introductionmentioning
confidence: 99%